Design and synthesis of Ni-MOF/CNT composites and rGO/carbon nitride composites for an asymmetric supercapacitor with high energy and power density1. Issue 26 (14th July 2015) - Wen, Ping; Gong, Peiwei; Sun, Jinfeng; Wang, Jinqing; Yang, Shengrong
<x xml:space="preserve">Abstract</x> Novel composites of Ni-MOF/CNTs and rGO/C3N4 were synthesized to assemble an asymmetric supercapacitor with high energy and power density.